From Workplace to Worthplace: Employee Disengagement in the Light of the Rule of Benedict - Rock, Michael Edward (Université Saint-Paul / Saint Paul University, 2016)
A discussion of the Rule of St. Benedict, emotional intelligence and workplace spirituality research to facilitate the shift from a workplace to a worthplace.
Keywords: Rule of Benedict; emotional intelligence; workplace spirituality research; personalism